Dermatopathology - Elston, Dirk M.; Ferringer, Tammie C.; Ko, Christine J.; High, Whitney A.; DiCaudo, David J.; Bhuta, Sunita (St. Louis : Elsevier, 2025)
Dermatopathology, Fourth Edition offers a clear and accessible introduction to this complex subspecialty, combining concise text with extensive labeled image collections and online lectures. Presented in an outline atlas format, it provides high-resolution histopathology examples, key diagnostic points, and updated coverage of soft tissue tumors and new entities. With over 1,300 images in print, additional online atlases, and interactive learning tools, it serves as an ideal resource for exam preparation and accurate clinical practice. Provides new flashcards online to test your knowledge and identify areas for further review. An eBook version is included with purchase. The eBook allows you to access all of the text, figures, and references, with the ability to search, customize your content, make notes and highlights, and have content read aloud.
Obsahuje QR kód s prístupom k rozširujúcim materiálom
Obsahuje bibliografie a register
Keywords: choroby kožné -- patológia; histológia; nálezy morfologické a mikroskopické; dermatológia; histopatológia; atlas